Meta Analysis: Effect's of Verbal and Physical Violences on Depression in Postpartum Women - Putri, Ebtaria Hartiwi; Demartoto, Argyo; Murti, Bhisma (Journal of Maternal and Child Health, 2023)
Background: Postpartum violence can manifest in many forms, including verbal, physical, and emotional abuse, as well as inappropriate clinical practice. This study aims to analyze previous primary studies in assessing the effect of verbal violence and physical violence on the incidence of depression in postpartum women.Subjects and Method: This study is a systematic review and meta-analysis using the PRISMA flow chart and the PICO model. Population: postpartum women. Intervention: experiencing verbal violence and physical violence. Comparison: not experiencing verbal violence and physical violence. Outcome: depression. The online databases used are PubMed, SpringerLink, Scopus and ProQuest with the keywords “Verbal Abuse” Verbal Violence” OR “Intimate Partner Violence” AND “Physical Violence” OR “Physical Intimate Partner Violence” OR “Domestic Violence” OR “Physical Abuse” AND depression OR “Post Tramumatic Stress Disorder” AND “Postpartum” AND “Cross sectional” AND “aOR”. There were 12 cross-sectional studies published in 2016-2022 that met the inclusion criteria. The analysis was carried out using the Review Manager 5.3 application.Results: Meta-analysis was carried out on 12 articles with a cross-sectional study design from Malaysia, South Africa, Japan, Brazil and Spain. The results showed that postpartum women who received verbal violence were more likely to experience depression 2.89 times than those who did not experience physical violence (aOR= 2.89; 95% CI = 1.96 to 4.25; p= 0.001) and postpartum women who received physically abused were 2.29 times more likely to experience depression than those who did not experience physical violence (aOR = 2.29; 95% CI = 1.37 to 3.83; p= 0.002).Conclusion: Verbal violence and physical violence can affect the incidence of depression in postpartum women. Keywords: postpartum women, verbal abuse, physical abuse, depression. Correspondence: Ebtaria Hartiwi Putri, Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email: ebtariahartiwi273@gmail.com. Mobile: +6289666588614.